THE CLASSIFICATION OF ENGLISH CONSONANTS - Teshaboyeva Nafisa Zubaydulla qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article presents a detailed classification of English consonants based on three primary phonetic criteria: place of articulation, manner of articulation, and voicing. Each category is explored to explain how different English consonant sounds are produced in the vocal tract. By identifying key features such as bilabial, alveolar, and glottal articulations, as well as voiceless and voiced distinctions, the classification provides a foundational understanding of English phonetics. This structured approach aids in language acquisition, phonetic analysis, and speech therapy, highlighting the importance of consonant classification in linguistics and language learning.